ESCRITA DE TEXTOS TEATRAIS : Material didático em Ambiente Online sob uma perspectiva BIPOC - ROCHA, Danilo José Assunção da (Universidade Federal do Pará, 2025)
The present work aims to develop educational material for an online course that introduces the writing of drama texts for BIPOC individuals - acronym in English referring to Black, Indigenous, and People of Color. By understanding language as a social and historical product, a vehicle for ideological representations in which materialization manifests through discourse (FIORIN, 1990), this dissertation addresses the study of ramaturgy and proposes to investigate the theme as part of the phenomenon of dramatic theater (MAGALDI, 1994) and its possibilities in conveying discourses. Grounded in the intersections between Art, Education, and Digital Technologies, the hybrid methodology action research (THIOLLENT, 2011) combines bibliographic research on drama as a textual genre, online education (KENSKI, 2012), and design (KENSKI, 2012; PAWAN, 2012) to create the didactic-dramaturgical material in digital space (ØSTERN, 2021). The development of this material, with key elements and teaching strategies to introduce the writing of theatrical dramaturgy in an open learning environment, seeks to promote access to the mentioned knowledge and democratize artistic creation, as well as contribute to perspectives related to the use of technological tools in writing.